Feasibility of Oil Mud Reinjection from Offshore Platforms in Bohai Oilfield - Jiao, Guoying; Zhu, Shijie; Wang, Jun; Huang, Zhuangzhuang; Xu, Mei (Journal of Basic & Applied Sciences, 2023)
Sludge produced by offshore oilfields can be difficult to treat. thus, it is necessary to explore the feasibility of its reinjection into reservoirs for environmental protection and economic benefits. In this study, oil sludge produced from an oilfield in the Bohai Sea was ground and refined, and a reinjection system using a polymer solution was developed. To determine the feasibility of the reinjection system, we analysed its stability, solution performance, injection performance, and oil displacement effect. The experiment results indicate that when the particle concentration of the system is ≤ 200mg/L, the system dispersion, anti-shearing, and anti-ageing stability can be enhanced. When he particle concentration is ≤100 mg/L, the system can easily manage the viscous nature of the solid particles, thereby achieving optimal stability. At a particle concentration of 100mg/L, the system can run with optimal performance and achieve good oil displacement efficiency. Therefore, a system with a particle concentration of 100mg/L can be used for long-term reinjection of offshore platforms in the Bohai oil reservoir, achieving environmentally friendly treatment of produced sludge while further enhancing the oil recovery rate of the reservoir.